Tackling gender inequality in community-based organizations: The contribution of cacao cooperatives to environmental justice for women in Peru - Miram Maeder; Thomas, Evert; Villar, Gesabel; Ramírez, Marleni; Fünfgeld, Hartmut; Oberlack, Christoph (Ubiquity Press, Ltd., 2024)
Persistent gender inequalities challenge theory and praxis of community-based collective action. Here we adopt an innovative approach which integrates environmental justice, value chain inclusion and collective action theory to diagnose inequalities in community- based organizations (CBOs) and identify strategies to address them. Drawing on the findings of case studies conducted at six CBOs in Peru’s cacao sector, this article aims to make three contributions. Empirically, we analyze the current situation of, barriers to and strategies for environmental justice for women in the six selected CBOs. Theoretically, we contribute to theory on community-based collective action through an analysis of environmental justice and value chain inclusion. Methodologically, we propose a framework that analysts may use to assess environmental justice for women in community-based collective action. Results show that overall, women participate less and benefit less from cacao CBOs. Furthermore, recognition of women’s contributions and capabilities for cacao value creation tend to remain limited. We discuss 18 strategies and recommendations through which CBOs can address gender inequality for their female stakeholders on a cooperative, community, household and individual level. Most salient recommendations include workshops, generating income opportunities for women, increasing the rights of partners of official cooperative members, and introducing quotas for women in leadership positions. If such efforts are reinforced and better theorized, and gender strategies continuously implemented, CBOs such as cacao cooperatives have the potential to improve the environmental justice outcomes for women within their organizations, families, and communities at large.